(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: Management of obstructive jaundice from periampullary and pancreatic head malignancies is mostly palliative. With advancements in endoscopic and stent technology and instrumentation, endoscopic interventions are gaining popularity and acceptance over surgical relief of jaundice. Objective: To study efficacy of surgical biliary bypass over biliary metallic stents for palliation of incurable malignant distal bile duct obstruction. Materials and Methods: Prospective observational study was carried out among 77 patients withincurable malignant distal bile duct obstruction. 45 of them chose to undergo surgical bypass while 32 agreed to undergo metallic stenting. Parameters like improvement in jaundice, procedure related morbidities, need for re-hospitalization, need for re-intervention, quality of life and survival were compared in two groups. Chi square test and t test were applied to compare two groups. Results: There was prompt and good relief of jaundice in both groups. There was one procedure related mortality in each group. The morbidities were comparable. The stented patients were hospitalized for a cumulative mean period of 34.1 days compared to 14.2 days in the surgical bypass group (p= 0.0001). The global quality of life, pain, nausea, vomiting and appetite were significantly better in the surgical bypass group. There was significantly improved overall survival in the surgical bypass group (163.5 days vs. 150 days, p= 0.0001). Conclusion: Surgical bypass offers safe and superior palliation to obstructive jaundice from inoperable periampullary and pancreatic head cancer.